Praca socjalna i poradnictwo prawne w pomocy rodzinom dysfunkcyjnym - Rajewska de Mezer, Joanna (Wydawnictwo Naukowe UAM, 2016)
The influence of parents, families on the development of the individual and social identity of their child is extremely important. In the process of primary socialization, child acquires patterns of social roles, which modifying plays in its adulthood. Dysfunctional family is not able to perform its functions (socialization, educational, protective) properly, what can be harmful for children. In order to prevent child from the negative effects of dysfunction, family should be covered with a professional help. This assistance should base on the principle of subsidiarity and stimulates family to cooperation and activity in the exit of a difficult situation. Support in this area provide social assistance entities, using social work and legal advice. This form of support can equip the beneficiary professional knowledge, allow him to realize the cause of the problem. It has also educational character.
Social Work and Legal Guidence as a Support for Disfunctional Families
Keywords: dysfunctional family; socialization; social care; social work; specialist advice; legal advice